A GIS-BASED ASSESSMENT OF THE SURFACE RUN-OFF VULNERABILITY IN THE BORDER AREA OF ANCIENT VOLCANO IMOGIRI SUB-DISTRICT, YOGYAKARTA, INDONESIA - Wardoyo, Muhammad Asrori Indra; Khotimah, Nurul (JURNAL GEOGRAFI Geografi dan Pengajarannya, 2026)
The Imogiri region originated from an ancient volcano and has subsequently transformed into a Fluvio-Volcanic plain. As an ancient environment significantly affected by external variables of a humid tropical climate, possible hazards such as geomorphological risks and surface runoff areas must be acknowledged. This study seeks to assess the vulnerability of surface runoff by determining the surface runoff coefficient by the Cook Method utilizing Geographic Information Systems. The Cook technique categorizes watershed features into three components to determine the runoff coefficient: topography, soil type, and vegetation cover. Data analysis employs the Geographic Information System (GIS) utilizing ArcGIS 10.3 software. The analytical results indicate that a value of C = 0.592 was achieved in 2025. In Imogiri Sub-District, 59.2% of precipitation is classed as surface flow, indicating a high value. Understanding the hazards associated with surface run-off is crucial for the implementation of effective and sustainable disaster management strategies. Keywords: Surface Run-off, Cook Method, GIS